PENGARUH UKURAN PARTIKEL CANGKANG KELAPA SAWIT TERHADAP EFISIENSI KALOR PADA BRIKET CANGKANG KELAPA SAWIT - Mustafa, Yoga Alun; Suwandi, Suwandi; Indah Utami, Amaliah Rohsari (Universitas Sebelas Maret, 2014)
The energy crisis is one of the problems facing mankind today. Because of the limitations of existing fossil energy on earth then much alternative energy development. One alternative energyi is developed briquettes. The briquettes are used in this study is the briquettes are made from raw material palm oil shell. Palm shell briquettes made by particle size variations. The measure used in the study are smaller than 8 mesh, between 8-12 mesh, between 12-20 mesh, and greater than 20 mesh. Grouping particle size sieve used to size 8 mesh, 12 mesh and 20 mesh. As the adhesives used briquettes cassava flour in the ratio 1:7 to palm shells. Briquettes with a mesh size of between 8 - 12 mesh has an average calorific value of the largest in the amount of 4696.2 cal / g. Briquettes with size greater than 20 mesh is the briquettes to trigger the shortest time and the amount of residual char slightly. Briquettes with size smaller than 8 mesh is briquettes with flame longest time with an average temperature of 65 â—¦ C.Â Keywords:Briquettes palm shells, large calorific value of briquettes, bomb calorimeter